Developing countries and the multinational trading system from the GATT to the Uruguay Round and the Future - Srinivasan, T N (New Delhi Oxford University Press, 1998)
Developing countries and the multinational trading system traces the history of the General Agreement on Tariffs (GATT)since its origin in 1947 and discuss the emergence of W.T.O.This issues also covered the Urugury Round Agreement.This book explains deve
Keywords: International trade; Trade regulation-Developing countries; Trde-Unions-Developing countries